2021
DOI: 10.36416/1806-3756/e20210129
|View full text |Cite
|
Sign up to set email alerts
|

Malignant pleural mesothelioma: an update

Abstract: Malignant mesotheliomas are rare types of cancers that affect the mesothelial surfaces, usually the pleura and peritoneum. They are associated with asbestos exposure, but due to a latency period of more than 30 years and difficult diagnosis, most cases are not detected until they reach advanced stages. Treatment options for this tumor type are very limited and survival ranges from 12 to 36 months. This review discusses the molecular physiopathology, current diagnosis, and latest therapeutic options for this di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 173 publications
(218 reference statements)
2
16
0
Order By: Relevance
“…Saitoh et al [23] reported 2 patients diagnosed as malignant peritoneal mesothelioma [15] and 3 patients from the general population (control cases) who died from other causes. The cases were 2 males and 3 females.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saitoh et al [23] reported 2 patients diagnosed as malignant peritoneal mesothelioma [15] and 3 patients from the general population (control cases) who died from other causes. The cases were 2 males and 3 females.…”
Section: Resultsmentioning
confidence: 99%
“…Malignant mesothelioma is linked to exposure to asbestos in a large proportion of cases, most of which concern pleural tissue (73-85%), with the peritoneum being the second most affected site (7-18% of total cases) [7,15].…”
Section: Introductionmentioning
confidence: 99%
“…Current investigations in the realm of CPIs encompass not only those targeting T-cell responses or activating T-cell pathways but also the utilization of cytokines such as IL-12 and IL-15, therapeutic vaccines, ablation of immunosuppressive cells, and modulation of other constituents of the immune cascade. 11 …”
Section: Immune Checkpoint Inhibitors (Cpis)mentioning
confidence: 99%
“…1 The malignant potential of asbestos fibres lies within their capability to deeply infiltrate the respiratory system and persist there for extended durations. 2 There is no known safe level of asbestos exposure. 3 …”
Section: Introductionmentioning
confidence: 99%